Robust Control Design of Nonlinear System by Using Back-Stepping-GSA and Sliding Mode Technique - Md Rozali, Sahazati; Mohd Nor, Rozilawati; Faiz Zainal Abidin, Amar; Kamarudin, Muhammad; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
This work presents the integration of two robust controllers such as back-stepping and sliding mode controller, which is designed for nonlinear system with external disturbance injected to its actuator. Gravitational Search Algorithm (GSA) is applied to the designed controller to optimize the control and reaching law parameters for the system. The dynamics of the system is developed by consider the external force as systemâ€™s nonlinearities. The tracking output and tracking error produced by combination of these two controllers is compared with the performance of classical sliding mode controller. Based on the results obtained, integration of these two controllers generates better performance than classical sliding mode controller based on its output and error.Â Â